FEATURES OF DEVELOPMENT OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCIES OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the research of communicative competence development peculiarities of the students of higher educational establishments. The paper describes 6 stages of training activity of the students based on the support materials as a means of educational and pedagogic purposes of training practice reaching.
Keywords: communicative competence; training practice; support materials